Trends and Determinants of Household Use of Financial Services in Ghana - Asiamah, T.A. (University Of Ghana, 2017)
Access to and use of formal financial services, namely savings, credit and insurance products, have far-reaching benefits for households and the economy at large. However, there is limited use of formal financial services and rather, a dependence on informal institutions of saving, borrowing and insurance in developing countries. In order to increase demand for formal financial services by households and micro enterprises, financial sector reforms were carried out extensively in the late 1980s and early 1990s in Ghana. Using the Ghana Living Standards Survey (GLSS) data and the Global Findex data, the study examined the trends in saving and borrowing by individuals from 1991 to 2014. Furthermore, using the Finscope Ghana 2010 data, the study employed Multinomial Logit regression in examining the factors that influence individuals' decision on saving, borrowing and insuring using formal versus informal institutions. Finally, the third, fourth, fifth and sixth rounds of the GLSS data were combined to examine the factors that influence the incidence of credit constraints among household heads, and also to assess changes in the incidence of credit constraints among female household heads over time. A Heckman Probit regression model was employed in the analysis. The results show a relatively stable trend in the proportion of individuals that saved from 1991 to 2006. However, from 2006 to 2013, there was a large increase in the proportion that saved. There was an oscillating trend in the pattern of borrowing from 1991 to 2014. Over the years, there was a general decline in the proportion of individuals that borrowed from informal institutions, and an increase in the proportion that borrowed from formal institution. Over the years, a lower proportion of females and rural residents saved when compared to the proportion of males and urban residents that saved. Similarly, a lower proportion of the poor saved and borrowed from all kinds of institutions than the non- poor. Furthermore, the poor, particularly in rural areas were more likely to face credit constraints than the non-poor. The study provides support for the life-cycle hypothesis both cross-sectionally and over time. Financial literacy increases the probability of using financial services from formal institutions. Education and wage or salaried employment also increases the probability of saving and insuring in formal institutions, while non-salaried employment increases the probability of saving and insuring in informal institutions. Rural residents were generally more likely to save with informal institutions. In urban areas, females and individuals with low education were more likely to save with informal institutions, whilst in rural areas, those who were previously married, such as the divorced, separated or widowed were more likely to use informal saving institutions. In both urban and rural areas, recipients of local remittances were more likely to save in informal institutions. When it comes to the use of credit, the aged in urban areas were less likely to borrow from all kinds of institutions. Individuals who had negative experiences with financial institutions were more likely to borrow from informal institutions. For insurance, the lack of understanding of insurance increased the probability of insuring with informal institutions. The study also showed that having tertiary education as a household head reduces the incidence of credit constraints. Furthermore, the poor, widows and those who had separated or divorced in rural areas were more likely to face credit constraints. The aged in urban areas also had higher probability of facing credit constraints. In the general population, females were generally less likely to face credit constraints than males. However, the incidence of credit constraints among females increased in 2012 relative to 1991. The study recommends the promotion of financial education and formal education to enhance the use of formal financial services. The study also recommends the design of credit products to suit the needs of the poor, widows, the divorced or separated in rural areas, as well as the aged in urban areas. Finally, the study recommends the intensification of programs that support rural financial institutions in order to increase access to formal saving products by rural residents.
Thesis (PHD.)
Keywords: Rural Residents; Financial Services; Households; Informal Institutions; Savings; Borrowing; Insurance; Ghana